Determinants of energy efficient appliances among Malaysian households: Roles of theory of planned behavior, social interaction and appliance quality - Siti Aminah, Harun; Muhammad Ashraf, Fauzi; Nur Muneerah, Kasim; Wider, Walton (Asian Economic and Social Society, 2022)
The purpose of this study is to investigate the determinants of purchasing intention of energy efficient appliances among Malaysian households. Consumer behavior, particularly when purchasing non-environmentally friendly products, contributes significantly towards environmental problems and climate change. This study adopts the theory of planned behavior as the basis and integrates it with two external domains, namely social interaction and the quality of energy efficient appliances. A total of 318 respondents participated and were analyzed via partial least squares structural equation modeling (PLS-SEM). Findings show that perceived behavioral control and subjective norms exert a significant and positive effect on consumers’ intention to purchase energy efficient appliances, while attitude has no significant influence. Meanwhile, social interaction and quality were found to be critical determinants of intention to purchase energy efficient appliances. Implications in the context of sustainable purchasing behavior and recommendations to increase consumers’ purchases of energy efficient appliances or green appliances are discussed.